Fitness industry: state and prospects of development in the countries of the world - Liubov Chekhovska (Kharkiv State Academy of Physical Culture, 2017)
Fitness industry is a sphere of successful and promising business in many countries around the world. That is why it is necessary and relevant to study the prospects for the development of the international fitness industry. Purpose: to study the state of functioning and prospects for the development of the fitness industry in the world. Material & Methods: theoretical analysis and generalization of scientific literature, sources and information of the world internet, documentary method, system analysis method, comparison and compare method. Results: the article presents an analysis of the fitness market in different countries in the world. The volume of the market is determined by the number of fitness clubs, the number of clients and profitability. Examines the key trends in the industry of sports services, its economic performance. The top 20 most popular fitness networks of the world are determined. Describes the fitness industry in the US and Russia. Conclusion: fitness industry in various countries of the world develops and strengthens positions on the world arena, during 2012-2016. concluded the most successful transactions. The total revenue of the fitness industry in 2015 was 81 billion dollars. In 2016, most European operators of fitness clubs expected financial growth.